Histopathological and immunohistochemical characterization of lesions in the golden Syrian hamster model of Nipah virus infection (Bangladesh strain) - Swan, Kirsty; Salguero, Francisco Javier; Bird, Alison; Hunter, Laura; Kennard, Chelsea; Findlay-Wilson, Stephen; Kennedy, Emma; Kempster, Sarah; Almond, Neil; Dowall, Stuart; Ruedas-Torres, Inés (Frontiers in Veterinary Science, 2026)
Nipah virus (NiV) is recognised as a priority pathogen with pandemic potential by the World Health Organisation (WHO). The NiV-Bangladesh strain (NiV-B) has been associated with recent outbreaks in different districts of Bangladesh and the state of Kerala (India), and it is suggested to be more pathogenic and lethal than the NiV-Malaysian strain (NiV-M). In this study, we aimed to describe the clinical signs and pathology of NiV-B using the golden Syrian hamster model following intranasal (IN) and intraperitoneal (IP) inoculation with different doses and to compare with prior NiV-M results. For this purpose, we selected samples from NiV-B-infected animals that were submitted for H&E evaluation, immunohistochemistry (IHC), in situ hybridisation (ISH) (RNAscope technique), and multiplex immunofluorescence (mIF). The absence of neurological signs was observed in NiV-B-infected animals compared with those that were NiV-M-infected. Except for the brain, which did show only mild lesions, histopathological analysis of NiV-B demonstrated similar pathology and viral RNA in the lung, spleen, and liver compared to those of NiV-M infected animals, with the lung being the main affected organ. Pulmonary lesions consisted of areas of broncho-interstitial pneumonia associated with high cell death activation (caspase-3), proliferation (Ki67), and abundant intralesional macrophages (Iba1) and T cells (CD3). Differential upregulation of the cytokine IL-6 was observed in the lung from NiV-B compared with NiV-M infected animals. Moreover, we demonstrated the wide distribution of the NiV receptor ephrin B2 in endothelial cells, neurons, smooth muscle, epithelial cells, macrophages/type II pneumocytes, and T cells.